2016
DOI: 10.1016/j.biochi.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of two large antiviral polyamides with the long control region of HPV16

Abstract: PA1 and PA25 are large hairpin polyamides that are effective in nearly eliminating HPV16 episomes (DNA) in cell culture, and PA25 has broad spectrum activity against three cancer-causing forms of HPV (Edwards, T. G., Koeller, K. J., Slomczynska, U., Fok, K., Helmus, M., Bashkin, J. K., Fisher, C., Antiviral Res. 91 (2011) 177-186). Described here are the interactions of these PAs with sequences in the long control region (LCR) of HPV16 (7348-122). Using an FeEDTA conjugate of PA1 (designed to recognize 5’-W2GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…9,26 The first biophysical studies of PA25 were reported recently. 18b However, PA25 is a more difficult synthetic and purification challenge than PA1 and its derivatives, though we have scaled up both PA1 and PA25 to 10 g, and the cost-of-goods is much higher for the 20-ring PA25 than the 14-ring PA1 , so we were interested to see if modifications to PA1 could increase its activity significantly. That goal was successful with PA31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9,26 The first biophysical studies of PA25 were reported recently. 18b However, PA25 is a more difficult synthetic and purification challenge than PA1 and its derivatives, though we have scaled up both PA1 and PA25 to 10 g, and the cost-of-goods is much higher for the 20-ring PA25 than the 14-ring PA1 , so we were interested to see if modifications to PA1 could increase its activity significantly. That goal was successful with PA31 .…”
Section: Discussionmentioning
confidence: 99%
“…18 In fact, in that prior work we found for 14-ring PA1 that numerous “mismatch” sites were bound with higher affinity than so-called canonical sites. Also, up to four mismatches were tolerated with 2 nM dissociation constants identical to numerous “perfect-match” sites.…”
mentioning
confidence: 87%
See 3 more Smart Citations